2004
DOI: 10.1021/tx049745z
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of Rodent Pulmonary Tissue Following Bis-(2-chloroethyl) Sulfide Exposure

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defense, Washington Headquarters Services, Directorate for Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 40 publications
1
45
0
Order By: Relevance
“…The increased ROS we have seen in mitochondria may be because of mitochondrial dysfunctional, which we have seen in our CEES model and what others have seen after SM exposure (Sourdeval et al, 2006). The mitochondrion, specifically the respiratory chain, can produce a substantial amount of endogenous ROS (Fridovich, 1978;Drose and Brandt, 2008), and, if CEES causes mitochondrial uncoupling, this could explain oxidation products seen in other areas of the cell and markers of apoptosis (Dillman et al, 2005;Sourdeval et al, 2006). This idea is supported by recent findings that suggest sulfur and nitrogen mustards can react with cellular reductases and increase free radical production (Brimfield et al, 2009).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The increased ROS we have seen in mitochondria may be because of mitochondrial dysfunctional, which we have seen in our CEES model and what others have seen after SM exposure (Sourdeval et al, 2006). The mitochondrion, specifically the respiratory chain, can produce a substantial amount of endogenous ROS (Fridovich, 1978;Drose and Brandt, 2008), and, if CEES causes mitochondrial uncoupling, this could explain oxidation products seen in other areas of the cell and markers of apoptosis (Dillman et al, 2005;Sourdeval et al, 2006). This idea is supported by recent findings that suggest sulfur and nitrogen mustards can react with cellular reductases and increase free radical production (Brimfield et al, 2009).…”
Section: Discussionsupporting
confidence: 68%
“…More recent work with SM on DNA has characterized genomic changes that show increases in markers of apoptosis, cell cycle regulation, and various other response genes (Dillman et al, 2005). Furthermore, exploring the role of oxidative stress in CEES-mediated injury and supplementation with antioxidants as a treatment has been a major area of interest.…”
Section: Discussionmentioning
confidence: 99%
“…However, p53 is also activated in SM injury [10,[23][24][25]. Given that SM is known to damage DNA and the classical role of p53 is in cell cycle arrest and apoptosis, p53 has been widely implicated in SM-induced cell death [10,23,24,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, one clear benefit of microarray analysis is the potential to identify thousands of genes dysregulated in response to HD and, using mapping software, to characterize significantly altered pathways. Early microarray studies identified pathways such as inflammation, apoptosis, protein catabolism, and cell cycle as involved in HD-induced toxicity (Rogers et al, 2004;Dillman et al, 2005). Likewise, genomics efforts from our group are now focused on assessing how HD exposure dose and time affect these signaling pathways.…”
Section: Genomics Applications To Cwasmentioning
confidence: 99%